Pelatihan Menulis Artikel Ilmiah dan Publikasi Kegiatan Pengabdian Masyarakat - Rahmatullah, Rahmatullah; Putri, Hardiyanti; Herayanti, Lovy (Indonesian Publication Center, 2025)
Writing scientific articles is an important skill for students. Students must publish their completed community service activities (KKN) in a journal system. However, field findings indicate that many students still experience obstacles and lack a profound understanding of writing and publishing scientific articles. This activity was presented with the aim of providing students with an understanding of writing scientific articles and publications. Participants were general students from various universities. The training was conducted online using the Google Meet platform. The training lasted two days, with an additional day to receive the articles that had been written and published. Data collection techniques used triangulation (observation, interviews, and documentation) with the additional assistance of a questionnaire. The results of the activity indicated that the training participants experienced an increased understanding of writing scientific articles. Participants felt helped and were enthusiastic about writing scientific articles without significant anxiety. Many of their articles were published in nationally accredited journals.